Influence of structural parameters on the vertical pounding between girder and pier in unequal-span girder bridges under near-fault vertical ground motions - Lin Zhang; Wei Zhang (Scientific Reports)
Abstract This study investigates the vertical pounding response of unequal-span girder bridges, focusing on the effects of rubber bearing stiffness, span ratio, and pier height. With a continuous model simplified and constructed, theoretical solutions for the bridge’s vertical pounding responses are then implemented. Results show that the local contact stiffness between the girder deck and pier is highly correlated with the bridge bearing, affecting the frequency and force of vertical pounding. Additionally, the span ratio impacts the number and magnitude of poundings, with an optimal range identified to minimize the bridge damage from the impact. Additionally, while having minimal effect on the natural period and pounding zone position, pier height significantly influences the amplitude of the pounding force, with higher piers experiencing more frequent but less intense pounding and vice versa. This research underscores the importance of considering vertical earthquake effects in bridge design and provides valuable insights for enhancing the resilience of unequal-span girder bridges.